Liquidity Solvency Market Value and Firm Size on Stock Prices: Likuiditas, Solvabilitas, Nilai Pasar, dan Ukuran Perusahaan terhadap Harga Saham - Ellanda Martha Adelia; Eny Maryanti (Indonesian Journal of Innovation Studies, 2025)
General Background: Stock price movements in the capital market are closely associated with corporate financial performance and investor perceptions reflected in financial ratios and company characteristics. Specific Background: Pharmaceutical companies listed on the Indonesia Stock Exchange require strong financial performance indicators to maintain investor confidence and support stock valuation. This study examines profitability, liquidity, solvency, market value, and firm size in relation to stock prices during the 2017–2021 period. Knowledge Gap: Previous studies concerning financial ratios and stock prices have reported inconsistent findings, particularly regarding profitability, liquidity, solvency, market value, and firm size in pharmaceutical companies. Aims: This study aims to determine the relationship between profitability, liquidity, solvency, market value, and firm size with stock prices in pharmaceutical companies listed on the Indonesia Stock Exchange. Results: The findings show that profitability does not have a significant relationship with stock prices, while liquidity, solvency, market value, and firm size are associated with stock prices. The regression analysis also indicates that the research model explains a substantial proportion of stock price variation. Novelty: This study integrates profitability, liquidity, solvency, market value, and firm size within a single quantitative model focusing specifically on Indonesian pharmaceutical companies during the 2017–2021 period. Implications: The findings provide relevant insights for investors, corporate management, and capital market stakeholders in evaluating financial indicators related to stock price movements in the pharmaceutical sector.Highlights: Profitability showed no significant association with share valuation. Current ratio, debt ratio, and PER were linked to market movements. Corporate scale was statistically related to equity trading performance. Keywords: Stock Prices; Pharmaceutical Companies; Liquidity; Solvency; Market Value